THE ANALYSIS OF THE EFFECT OF RAINFALL AND LOAD IMBALANCE TOWARD AN ELECTRICAL POWER LOSS AT PT. PLN (PERSERO) ULP BUMIAYU.: Array - Putra, Yogi Ade; Noor Prasetyono, Rizki; Adzin Murdiantoro, Randi (Program Studi Teknik Elektro Universitas Peradaban, 2022)
Electrical energy is a very essential energy where almost all human needs are related to it. The distribution of electricity in both of transmission and distribution networks are expected to operate optimally and continuously. The constraints in the distribution of electrical energy are usually caused by several factors, including rainfall and load imbalances. The data on the value of rainfall and load imbalance will later be analyzed with the value of electrical power loss. This study aims to determine whether rainfall and load imbalance affect the electrical power loss. By knowing the value of these constraints, it will be analyzed with the value of electrical power loss. The type of research used is quantitative analysis research using multiple linear regression test.. Based on the results of linear regression analysis in the summary model, ANOVA, the coefficient showed a rainfall significance value of less than 0.05, it meant that there was no significant effect on electrical power loss and a load imbalance significance value of more than 0.05, mit showed that there was a significant effect on power loss electricity. Meanwhile, the percentage of influence of the independent variable of rainfall and load imbalance on the dependent variable of power loss was 9,4% and the remaining 90,6% was influenced by other variables not examined.